1995
DOI: 10.1046/j.1365-313x.1995.8040583.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of freezing‐tolerance‐associated proteins in the cytoplasm and nucleoplasm of wheat crown tissues

Abstract: SummaryA protein family associated with the development of freezing tolerance in wheat has been identified. This protein family is Gramineae-specific and coordinately regulated by low temperature. Antibodies directed against the 50 kDa (WCS120) protein recognize at least 5 members of this family. Using these antibodies, the cellular content and location of this protein family was determined in coldacclimated wheat seedlings. Western analyses of subcellular fractions indicated the presence of all members of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
146
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(160 citation statements)
references
References 12 publications
13
146
0
1
Order By: Relevance
“…DHNs localize primarily to the nucleus or cytoplasm (Houde et al, 1995;Bracale et al, 1997), but studies also corroborate their presence either in the plasma membrane (Danyluk et al, 1998), endoplasmic reticulum (Neven et al, 1993), chloroplast (Wisniewski et al, 1999), mitochondria (Borovskii et al, 2002) or even in the vacuole (Heyen et al, 2002). DHNs may thus be expressed either constitutively [e.g.…”
Section: Structure and Functional Studies Of Dhnamentioning
confidence: 91%
See 1 more Smart Citation
“…DHNs localize primarily to the nucleus or cytoplasm (Houde et al, 1995;Bracale et al, 1997), but studies also corroborate their presence either in the plasma membrane (Danyluk et al, 1998), endoplasmic reticulum (Neven et al, 1993), chloroplast (Wisniewski et al, 1999), mitochondria (Borovskii et al, 2002) or even in the vacuole (Heyen et al, 2002). DHNs may thus be expressed either constitutively [e.g.…”
Section: Structure and Functional Studies Of Dhnamentioning
confidence: 91%
“…Arabidopsis DHNX] or confined to the root tip (ERD14 and LTI29), vascular tissues (ERD14, LTI29 and RAB18) and stomatal guard cells (RAB18). DHNs accumulate within vascular tissues (Godoy et al, 1994;Houde et al, 1995;Danyluk et al, 1998;Nylander et al, 2001), pollen sacs, guard cells and root meristems (Nylander et al, 2001), endosperm and zygotic embryos of mature seeds, developing root primordia (Godoy et al, 1994;Bracale et al, 1997), wheat crown tissues (Houde et al, 1995) and peach shoots (Wisniewski et al, 1999). DHNs found only in the cytosol include those of C. plantagineum DSP16 (Schneider et al, 1993) and rice RAB21 (Mundy and Chua, 1988).…”
Section: Structure and Functional Studies Of Dhnamentioning
confidence: 99%
“…Some COR proteins, like Arabidopsis KIN1, show structural similarities to antifreeze proteins (Kurkela and Franck, 1990) and others to a HSP70 chaperon family which is known to have roles in protein transport, folding and assembly/disassembly processes (Neven et al, 1992). Although physiological function of these different classes of COR proteins remains largely unknown, some showed a positive correlation with the degree of freezing tolerance which is enhanced by cold acclimation (Monroy et al, 1993;Houde et al, 1995;Jaglo-Ottosen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…DHNs have been found in the cytoplasm (12), nucleus (12,13), mitochondria (14), vacuole (15), and chloroplasts (16). They are known to associate with membranes (17,18), proteins (19) and excess salt ions (15,20).…”
Section: Introductionmentioning
confidence: 99%
“…Pekinensis (21). Many studies have reported a positive correlation between the accumulation of DHN transcripts or proteins and tolerance to freezing, drought, and salinity (12,17,(22)(23)(24). Moreover, modulation of transcripts by light has been reported for many DHN-encoding genes in drought-or cold-stressed plants (25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%